Breeding and genetic diversity in Chrysanthemum morifolium in India : A review - DATTA, S K; JANAKIRAM, T (The Indian Journal of Agricultural Sciences, 2015)
Genetic diversity of any crop plays a very important role in developing new and novel desired forms through breeding and selection. Knowledge of diversity and its response to natural/human selection through hybridization is necessary for future breeding plan. All the present day colourful varieties of Chrysanthemum morifolium Ramat have been developed through complex interspecific crosses among elemental species, open pollination, indiscriminate intervarietal hybridization, spontaneous and induced mutation, selection and management of chimera. In floriculture industry there is always demand and necessity for new varieties. There is an urgent need for developing crop wise database. There is no record of total chrysanthemum varieties developed through classical breeding in different countries. Present article will provide maximum information generated in India on classical and mutation breeding on chrysanthemum along with important publications in chrysanthemum/floriculture by other research institutions/ universities.